Risk of Atherosclerosis and Helicobacter pylori Infection according to CD14 Promotor Polymorphism in Healthy Korean Population - Sung-Goo Kang; Woo Chul Chung; Sang-Wook Song; Kyu Re Joo; Hyewon Lee; Donghoon Kang; Joune Seup Lee; Kang-Moon Lee (Gastroenterology Research and Practice)
Background and Aim. We aim to elucidate the association of risk factors for atherosclerosis and H. pylori infection according to the promotor polymorphism of the CD14 gene in healthy Korean population. Methods. The patients who visited our hospital for routine health examinations and 266 healthy adults (170 males and 96 females) were enrolled in this study. The promotor polymorphism at −159C/T of the CD14 gene was determined by PCR-restriction fragment length polymorphism analysis. According to genetic polymorphism and H. pylori infection, we analyzed the risk of atherosclerosis. Results. The genotype frequencies were CC 7.9%, CT 45.1%, and TT 47.0%, respectively. There were no differences between specific genotypes of CD14 gene and H. pylori infection rate. As for HDL cholesterol level, there were significant differences among the three genotypes (P<0.01). In subjects with H. pylori infection, no significant differences were observed between specific genotypes of CD14 gene and the risk factors of atherosclerosis. Conclusion. The promotor polymorphism at −159C/T of the CD14 gene was associated with the risk factor of atherosclerosis in healthy Korean population. However, it was not associated with the rate of H. pylori infection and H. pylori induced atherosclerotic risk.